Learning based on problems in the Nursing Degree, is it really useful? - Mª Elisa de Castro Peraza; Mª Inmaculada Sosa Álvarez; Mª Remedios Afonso Martín; Ana Mª Perdomo Hernández; Mª Dolores Vera Iglesias; Julio Galiano García (Metas de Enfermería)
Objective: To determine the method acceptability of problem-based learning (PBL) for third-year students in the subject of 'Operating Room Nursing'; in order to assess whether it encourages self-learning, participation, interpersonal relationships and the advantages it represents. Material and methods: Cross-sectional study of students enrolled in the course 'Operating Room Nurses' (n = 49) of third grade. After dividing students into three groups, a case was presented that was studied in three sessions of two hours each. The assessment was performed using a specifically designed self-administered questionnaire, with 22 using a scale of 0 to 10 (very positive) and referred to the level of knowledge, teamwork mentoring and method acceptability . Descriptive statistics indices were calculated. Results: The response rate was 89.9%. Students felt that this approach improved their knowledge on the subject (mean: 9.14), their assimilative capacity of the subject (mean: 9) and individual self-learning (average: 8.82) and group (mean: 9) with participatory and respectful group dynamics in the tutoring (mean: 9.48). The overall assessment of PBL was 8.84. Conclusions: According to the students, the cases prepare them to face their professional future and increase their knowledge. The results show great satisfaction by the students. PBL helps to develop critical thinking and diagnostic judgment, promoting the development of attitudes and values.